“Earth Care, Babes ?”: Environmental sustainability in Instagram travel narratives - Yulianto, Wawan Eko; Sunardi, F.X. Dono; Amanda, Alodia Clea; Theofine, Irene; Damaris, Pricillia Tamara (citeus, 2025)
Throughout history, travel narratives have taken up various forms and served various purposes. The changes of forms and functions were influenced by the spirit of the age. Today, in the contemporary digital era, social media platforms like Instagram have transformed travel narratives into stories combining images and texts that significantly impact public attitude on travel and tourism. On certain occasions, Instagram travel narratives contribute to the dangerous trend of mass tourism, although there are moments when the same travel writing form advocates sustainability. This study investigates the extent to which travel narratives by prominent Indonesian travel influencers on Instagram advocate for sustainable tourism practices. Adopting a descriptive qualitative approach and employing the thematic analysis, this research analyzes textual and visual data within these narratives to analyze their alignment with the four pillars of sustainable tourism defined by the Global Sustainable Tourism Council (GSTC), i.e., sustainable management, socio-economic sustainability, cultural sustainability, and environmental sustainability. Findings revealed 1) a significant interest in sustainable tourism values among Instagram viewers, particularly environmental sustainability and 2) a strong focus on the sub-section of conservation of natural heritage, followed by resource management and waste and emissions management.